PRAKTIK ARISAN ONLINE SISTEM MENURUN DALAM PERSPEKTIF MASLAHAH (STUDI KASUS PADA ARISAN WAHYUNI SHOP DI DESA MENTIBAR KECAMATAN PALOH) - Yusnil; Munadi (Pascasarjana Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2020)
Along with the progress of the times and increasingly sophisticated technology, various arisan arisan, one of which is the declining arisan, where this arisan has appeared in Indonesia since 2016 which was initiated by socialite women in cyberspace or social media such as: Facebook, Instagram and Whatsapps Messenger. The focus of the problem in this research is how the online social gathering system practice has decreased at the Wahyuni ​​Shop arisan in Mentibar Village, Paloh District? 2. How is the maslahah review about the practice of online social gathering with a downward system in the perspective of maslahah at the Wahyuni ​​Shop arisan in Mentibar Village, Paloh District? This research method uses an approach in this research is to use a field approach (field research) with the type of descriptive research (qualitative), the community's understanding of the online social gathering practice system decreases in Maslahah perspective in Mentibar Village, Paloh District. The results of this study show that the online social gathering system practice decreased at the Wahyuni ​​shop arisan, more or less the same as the social gathering in general, where the online social gathering participants will get money according to the agreed sequence number. Each participant gets a different payment and the number of receipts, the initial serial number will pay more than the amount received and the final serial number will get a receipt greater than the amount to be paid. Apart from unequal dues, the provisions that have been made by the admin in the arisan must also be obeyed by every arisan participant. Analysis of Islamic law only two things are allowed (numbering system and admin fee) and others are not in accordance with Islamic law because in its implementation, each member of the arisan pays money with different nominal values, some benefit and some are disadvantaged.